Chat about Cars in Gran Turismo Indonesia Discussion Club: a Virtual Gemeinschaft in Netnography (Pembicaraan tentang Mobil di Gran Turismo Indonesia Discuss Club: Sebuah Virtual Gemeinschaft dalam Netnografi) - Muhammad Ardi Pritadi (IPTEK-KOM : Jurnal Ilmu Pengetahuan dan Teknologi Komunikasi, 2018)
The paper discusses the existence of Gran Turismo Indonesia Discussion Club (GTIDC) as a virtual gemeinschaft whose members like to play Gran Turismo (GT). Based on netnographical methodology, the research explains that offline activities of this group have developed certain norm, called fun culture, while the norms of the online ones are described as generalized reciprocity. Both norms are applied by routine activities of discussing the experience of driving cars in GT. Henceforth, this virtual gemeinschaft could be explained by physical-atomically analogy: the atom would be its social structure or virtual gemeinschaft, the flow rotation would be its discussion activities, the positive pole would be speaker or thread starter, and the negative pole would be commentators. Finally, the paper concludes that the social equilibrium could lead GTIDC to maintain social inclusion among its members. Nowadays, the use of social media like Facebook could establish such sociocultural phenomenon.